Simulation of Excavator Bucket Pressuring Through Finite Element Method - Suryo, Sumar Hadi; Bayuseno, Athanasius Priharyoto; Jamari, J.; Ramadhan, Gilang (Civil Engineering Journal, 2018)
Excavator bucket tool is one of the most important parts of an excavator. It is made of steel mixture. It is commonly equipped with protruding teeth on its cutting side to breakdown hard materials and also to prevent dryness and damage of the bucket. Excavator bucket tooth must have supporting geometrical shape to penetrate and to endure the digging process on the ground, gravels, stones, or any other abrasive field. It is because of the fieldâs natural characteristic when the bucket tool grinds the material. Mixed iron is common to be used as excavator bucket toolâs material because it is easy to get and economic. High hardness value is also needed on the surface that transports hard material such as mining equipment. Therefore, an accurate analysis should be done to determine the suitable material on this field. Design and analysis were done by using Computer-Aided Engineering (CAE) Abaqus 6.10 application to get the maximum tension as the result of loading. Analysis process to get the tension was done by adding 8285.06 N weight forces in static condition with the angle of 32o to the horizon. From the analysis it could be known that maximum tension experienced by excavator bucket tooth is 209.3 MPa, and it is still below the Maximum Equivalent von Mises stress so the design could be categorized as safe.